Quantified small bowel motility in patients with ulcerative colitis and gastrointestinal symptoms: a pilot study. (July 2021) - Tufvesson, Hanna; Dreja, Julia; Ekberg, Olle; Leander, Peter; Månsson, Sven; Ohlsson, Bodil
Background: Gastrointestinal (GI) symptoms are common in patients with ulcerative colitis (UC), even when the disease is in remission, possibly due to abnormalities in GI motility. Small bowel motility can be assessed globally and in specific intestinal regions during magnetic resonance enterography (MRE) using a displacement mapping technique. Purpose: To investigate whether small bowel motility in MRE differs between patients with UC and controls, and if altered motility correlates with GI symptoms. Material and Methods: In 2016–2018, patients who were admitted for MRE, regardless of clinical indication, were consecutively invited to the study. Healthy volunteers were recruited. The participants completed a questionnaire regarding GI symptoms and relevant clinical data were reviewed in the medical records. The dynamic imaging series obtained during MRE were sent for motility mapping and a motility index (MI) was calculated in jejunum, ileum and terminal ileum in all participants. Results: In total, 224 patients and healthy volunteers were enrolled in the study. Fifteen were diagnosed with UC and 22 were considered healthy controls. In UC, the prevalence of GI symptoms was higher than in controls ( P  < 0.001), both in remission and in active disease. There was no correlation between GI symptoms and small bowel motility in UC. Jejunal motility was lower in UC than in controls ( P  = 0.049). Conclusion: Jejunal motility is decreased in UC compared with healthy controls, but there is no relationship between small bowel motility and GI symptoms in UC.